Kerjasama Indonesia-Swiss Dalam Pembangunan Industri Pariwisata Di Wakatobi Periode 2013-2018 - Lesiana Septianty, Lesya (2020)
ABSTRACT Tourism is one that can increase economic growth in Indonesia, but in Indonesia still needs to be improved in the development of tourism industry. Indonesia has a diversity of biodiversity that is so beautiful, and not all tourist destinations in Indonesia are known by all the people including tourists. One of the places that is the best choice of destinations Indonesia has, namely Wakatobi, South East Sulawesi. However, it needs better development to improve tourism in Indonesia. This study saw how the Indonesia-Swiss cooperation in the development of tourism industry in Wakatobi. Swisscontact is one of the non-governmental organizations that helps developing countries. Swisscontact programs is to develop the tourism industry. The results of this research show the Indonesian-Swiss cooperation that has been carrying out its role well but due to internal factors, the area still needs to be remade through human resource training and private sector development in Wakatobi in the program called WISATA. Keywords: Swisscontact, WISATA, Tourism, Wakatobi.